Transmigration of copper T presenting as abdominal wall mass: a case report - Devi, T. Ramani; Banu, S. Shameema; Harini, T.; Kanimozhi, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Copper T is one of the widely used intra uterine contraceptive devices due to its safe, effective and reversible nature. It has also been widely used as it is cost effective too. Copper T is usually inserted immediate post-partum, post abortal, during the proliferative phase of any menstrual cycle or 6 to 8 weeks following post-partum. Complications associated with use of Copper T include heavy menstrual bleeding, pelvic inflammatory disease, uterine perforation, displacement and rarely, transmigration. Post-insertion of copper T, women need to have regular follow up visits to prevent such complications. Patients should be advised to check for the presence of threads periodically. Considerable number of patients with transmigration of copper T has been reported in literature. Sites into which transmigration has been reported include broad ligament, ovarian fossa, urinary bladder, sigmoid colon, rectum, peritoneum, omentum, pouch of douglas, retro peritoneal space, iliac veins, ovaries, appendix and rarely in the abdominal wall. Transmigrated copper T may be diagnosed with ultrasonogram, X-ray and CT scan. Copper containing intra-uterine devices are known to provoke inflammatory reactions and symptoms depending upon the sites to which they have been transmigrated. Hence, we should resort to early intervention and remove the misplaced copper IUCD at the earliest. Here, we are reporting a rare case of transmigration of copper T into the anterior abdominal wall elaborating on various facets of copper T including its advent, incidence of use, efficient diagnosis and well-planned retrieval.